Modified dynamic gracilis neosphincter for fecal incontinence: an analysis of functional outcome at a single institution - Mat Hassan, Mohd. Zailani; Rathnayaka, M.M.G; Deen, K.I (Springer, 2010)
Background: We undertook a prospective longitudinal study of patients with end-stage fecal incontinence who were undergoing transposition of the gracilis muscle as a neo-anal sphincter with external low-frequency electrical stimulation of the nerve to the gracilis combined with biofeedback. Methods: A total of 31 patients (21 male, 10 female: median age: 22 years; range: 4-77 years) underwent this procedure for treatment of traumatic disruption (11 patients, 35%), congenital atresia (11 patients, 35%), iatrogenic injury (6-20%), and perineal sepsis (3 patients, 10%). The gracilis muscle was transposed at operation in an alpha or gamma configuration. Low-frequency (7 Hz) transcutaneous electrical stimulation commenced 2 weeks after operation and was continued for up to 12 weeks. Biofeedback therapy, which consisted of supervised neosphincter squeeze exercises, commenced simultaneously and continued for up to 28 weeks. Outcome was assessed by clinical examination, anal manometry, the Cleveland Clinic Florida continence score (CCFS), and the Rockwood quality of life scale (FIQL). Successful outcome was defined by improvement in clinical outcome, patient satisfaction, a positive result on anal manometry, and/or CCFS < 9, or FIQL ≥ 4. Results: At median follow-up of 67 months, overall improvement was seen in 22 (71%). Maximum resting pressure (MRP) and maximum squeeze pressure (MSP) improved significantly after operation [MRP pre versus post, mean (SD), cm water-13.8 (9.6) versus 20.9 (11.3); P = 0.01; and MSP 36.6 (22.4) versus 95.4 (71.2), P = 0.001]. In a subset of 18 patients who showed improvement after operation, the CCFS score (mean, SD) improved from 19.2 (3.4) to 5.2 (5.6); P = 0.0001. FIQL (mean, SD) showed significant improvement in all four domains in 14 patients who reported improvement since the year 2000. Conclusions: A modified dynamic gracilis neoanal sphincter for end-stage fecal incontinence helps restore and sustain continence with improvement in quality of life in the majority of patients. The procedure was most effective as augmentation in those who had suffered a traumatic injury, when compared with patients with congenital atresia and sepsis that had resulted in loss of the native anal sphincter.